The Dynamics of Pedagogical Transformation of Teachers and Student Learning Experience in the P5 Project: A Thematic Analysis in the Era of Independent Learning - Hasmira Said; Pahenra A. Nongko; Yaman La Ndibo; Ridwan J. Deluma (FITK UIN Walisongo Semarang, 2026)
This research aims to explore in depth the pedagogical transformation of teachers and subjective experiences of students in the implementation of the Pancasila Student Profile Strengthening Project (P5) at Senior High School (SMA) Muhammadiyah Kota Kendari. Using qualitative approaches and thematic analysis, the research reveals how curriculum flexibility triggers a shift in the role of teachers from conventional teachers to more creative facilitators in designing contextual learning. The findings identified that P5 projects effectively create a